Problema Harta (MAAL) Keluarga Yang Disebabkan Perceraian Hidup dan Mati Dalam Pemahaman Fiqh Ulama Syafi’iyah dan Hanabilah - Ahmad Fauzi; Darmawan Tia Indrajaya; Kemas Muhammad Gemilang (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Family property in marriage is a necessity, so it must be clearly identified. Joint assets according to Law Number 1 of 1974 concerning marriage are limited to assets acquired during the marriage, while assets brought before the marriage takes place are called innate assets. In addition, family assets are also contained in the Compilation of Islamic Law in articles 85-97. As for knowing how to regulate family property in Islam, it is necessary to discuss the understanding of fiqh scholars from the Shafi'yah and Hanabila schools. As for the methodology of this research, it is included in the library research which is categorized as descriptive analytic with the method of analysis being qualitative. The data collection techniques are carried out in the library, such as reviewing books, journals and the like. The results of this study indicate that the scholars of fiqh have different opinions about the distribution of the various types of syirkah in the discussion of permissible and non-allowable partnerships (syirkah). Broadly speaking, the Egyptian Fuqaha (the majority are Shafi'i and Maliki schools), divide syirkah into four types, namely: syirkah 'Inan, syirkah Abdan, syirkah Mufawwadhah and syirkah Wujuh.